(untitled) (International relations and international law Journal, 2021)
The emergence in society of such new phenomena as the Internet and social media, having influenced the traditional structure of the diplomatic sphere, which has formed over years, served as the basis for the emergence of a new form of diplomatic service and the use of this form in the diplomatic service. In order to implement its internal and external political activities due to the use of the Internet and social media, the state, in the scientific society, especially in the field of international relations, has formed the “digital diplomacy” concept. The digital diplomacy concept, flowing into the “soft power” concept, contributed to the creation of a country image on the international stage. The article analyzes the activities of the French Ministry of Foreign Affairs, which is actively developing its image using digital technologies. The flaws in the use of digital technologies in the field of diplomacy in the Republic of Kazakhstan are considered. In the course of examining the topic, the authors used methods of analysis, collection and retrieval of facts and information, considered by them within the framework of the topic. The control method was also applied to analyze information in periodicals, assess the opinions of authors and systematize the latest points of view formed in headlines. Key words: digital diplomacy, soft power, Internet, social media, Ministry of Foreign Affairs, China,French State, Republic of Kazakhstan.